Vulvovaginal angiomyofibroblastoma: an uncommon benign mesenchymal tumour - Goh, Shanny; Ngan, Kah Wai; Mohtarrudin, Norhafizah; Mohd Ali, Razana (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
The female genital tract angiomyofibroblastoma (AMFB) is a rare benign mesenchymal tumour that mostly affects premenopausal women. Although it is most commonly seen in the vulvovaginal region, it has also been documented in the inguinosacral region, pelvis, and retroperitoneum (1,2). Patients usually present with indolent, painless swell- ing in the vulvovaginal region, or a pedunculated lesion on rare occasions. Those that appeared in the vulva were frequently misdiagnosed as Bartholin cysts. Leiomyoma is a differential in the vaginal area. AMFB must be recognised from aggressive angiomyxoma (AA) due to the latter’s potential for recurrence with typical infiltrative boundaries. We discuss a case of a 46-year-old woman who had a slow-growing paravaginal swelling incidentally discovered during a total hysterectomy for leiomyoma five years prior.